Atypical Spleen Hemophagocytic Histiocytic Sarcoma in a Dog - Stein, Heloize; Oliveira, Mariana Pires; Lasta, Camila Serina; Eckert, Juliana; Coradini, Juliana Sesana; Luz, Letícia Engelhardt; Contesini, Emerson Antônio; Pereira, Clairton Marcolongo (Acta Scientiae Veterinariae, 2021)
Background: The histiocytic sarcoma (HS) complex is a set of malignant neoplasms originating from interstitial dendritic cells or macrophages. When it involves macrophages of the splenic red pulp and bone marrow, it is referred to as hemophagocytic histiocytic sarcoma (HHS). HHS behaves more aggressively than HS and is usually fatal. HHS can be diagnosed by cytological and histopathological examination of neoplastic tissue. HHS is confirmed by immunohistochemistry using an anti-CD11d antibody. This neoplasm is often confused with immune-mediated hemolytic anemia or Evans syndrome due to erythrophagocytosis and platelet consumption. The clinical presentation of the animals progresses with evident anemia and thrombocytopenia, leading to signs such as prostration, inappetence, and pale mucosa, making diagnosis challenging and often late. This study aimed to report the clinic-pathological aspects of a canine with atypical hemophagocytic splenic HS. Case: A 4-year-old male Shih-Tzu canine was referred to the Veterinary Hospital with a history of prostration and anorexia. Pale mucous membranes were observed on physical examination. Blood tests revealed non-regenerative anemia, leukopenia, and thrombocytopenia. Serum protein levels were below the reference values for the species in biochemical examinations. Hemoparasitosis was suspected; however, the result of the polymerase chain reaction was negative. Abdominal ultrasound revealed a splenomegaly with heterogeneous parenchyma and a slightly irregular surface, but no visible mass in the spleen. Due to the difficulty of stabilizing the patient, even after successive transfusions, the animal underwent exploratory laparotomy with medial access and posterior splenectomy. Subsequently, the spleen was surgically removed, fixed in 10% buffered formalin, and processed routinely. Macroscopically, it had an irregular reddish-brown capsular surface. Histopathological examination of the spleen revealed a densely cellular neoplasm composed of round to spindle cells (histiocytes) arranged haphazardly in variably sized sheets separating the pre-existing spleen stroma. These histopathological findings were consistent with a histiocytic malignant neoplasm. Immunohistochemical analysis was performed to better define the origin of the histiocytic neoplasm. Neoplastic cells showed positive immunostaining of more than 80% of tumor cells for the CD11d antibody and weak immunostaining for CD11c and lysozyme. The patient survived for less than 30 days after the first hospital visit. Discussion: The diagnosis of HHS was based on the histological characteristics and positive immunostaining of more than 80% of the tumor cells for the CD11d antibody. HHS is an extremely aggressive and rare tumor that affects elderly dogs of any breed. In this study, HHS had atypical histologic characteristics, in which erythrophagocytosis and hemosiderin were not observed within macrophages. HHSs arise from macrophages of the red pulp of the spleen or bone marrow and express the b2 integrin, CD11d, and have low expression of CD1 and CD11c, which are predominantly expressed by non-hemophagocytic HS. The hematological and biochemical changes observed in this case were similar to those described in other dogs with HHS. Treatment of HHS is only palliative. Erlichia ewingii, E. canis, Anaplasma phagocytophilum, A. platys, Borrelia burgdorferi, Dirofilaria immitis, Leishmania infantum and immune-mediated hemolytic anemia are the main differential diagnoses because they cause anemia and thrombocytopenia accompanied by splenomegaly. Keywords: histiocytic sarcoma, spleen, immunohistochemistry, splenectomy, erythrophagocytosis.